Description Of Factors Affecting KB Acceptors In Selecting Condom Contraceptions - Marwidah; Andi Tenri Fajriani; Surianto Iskandar (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2019)
The choice of condom contraception makes husbands not satisfied with sexual intercourse. This shows that the husband's attitude is still negative towards the use of condom contraception that only thinks of himself, as well as the role of the wife in the use of condom contraception selection in intercourse which is still negative in the work area of ​​the Karassing Health Center. The population in this study was the husband of EFA active family planning acceptors who visited in the last 7 months (September 2017 - March 2018), the population in this study was 44 respondents, the sample of this study was 30 respondents. The sampling technique uses a probability sampling technique with a simple random sampling approach. This type of research is a descriptive study. Analysis to measure the wife's knowledge, attitudes, and support is univariate analysis. Good knowledge results as many as 11 respondents (36.7%), while sufficient knowledge of 10 respondents (33.3%), and lack of knowledge as many as 9 respondents (30.3%). The results of positive attitudes were 29 respondents (96.7%), while negative attitudes were 1 respondent (3.3%). The results of the wife's support received the support of 16 respondents (53.3%), while those who did not receive support were 14 respondents (46.7%). The conclusion of this study is,